Exploration of pre‐hospital patient delays in seeking care for symptoms of bacteremia and sepsis: A qualitative study. Issue 5 (8th December 2022) - Ruffin, Felicia; Van Horn, Elizabeth; Letvak, Susan; Kennedy‐Malone, Laurie
Abstract: Aim: We explored patient pre‐hospital delays in seeking care for symptoms of bacteremia and sepsis. Design: A qualitative descriptive study. Methods: In January 2021, we recruited a convenience sample of four men and six women who were former patients diagnosed with bacteremia. We conducted semi‐structured interviews by telephone. The tape‐recorded interviews were transcribed, coded and analysed using the Common‐Sense Model of Self‐Regulation. Data analysis continued until May 2021. Results: The three main themes included: gathering threads of information, weaving together the threads of information and impact and outcome of the illness. The main finding revealed was that an inability to recognize symptoms of bacteremia resulted in delayed help‐seeking. Participants had difficulty recognizing their symptoms as being related to bacteremia when they lacked experience with infection or could not differentiate them from symptoms of other chronic co‐morbid conditions. Recognizing symptoms and searching for their meaning was an early step in developing an action plan for seeking care. Patient‐reported physical and psychological outcomes of the infection on their quality of life (QOL) varied widely, from none to major impact.